Comparison of Giving Coconut Water and Honey to First Trimester Pregnant Women in Reducing Hyperemesis Gravidarum at Pratama Regency Medical Clinic in 2023 - Amalia Indah Puspitasari; Pirli Sawitraningsih; Sukarni Setya Yuningsih (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
The incidence of hyperemesis gravidarum in Indonesia reaches 14.8% of all pregnancies In West Java there are 56.60% of pregnant women out of 121,000 with hyperemesis gravidarum, and in Bekasi Regency there are 50.21% of pregnant women who experience hyperemesis gravidarum out of a total of 26,231 pregnant women(1). Hyperemesis gravidarum can be treated using pharmacological therapy and non-pharmacological therapy. Non-pharmacological treatment therapy that can reduce hyperemesis gravidarum is consuming coconut water and honey. To find out the comparison of giving coconut water and honey to pregnant women in the first trimester in reducing hyperemisis gravidarum. Method uses quasi experimental with a pretest protest design with two experimental design. The sample in this study was all 30 pregnant women in the first trimester at the Pratama Regency Medical Clinic in November 2023 - January 2024, the sampling technique was total sampling. There is a difference in giving coconut water and honey to pregnant women in the first trimester in reducing hyperemisis gravidarum (p.value 0.000). After the comparison between the groups given coconut water and honey, it was concluded that coconut water was more effective in reducing hyperemisis gravidarum than honey with a difference of 6.07 in the coconut water treatment and 1.50 in the honey treatment, which was 4.567.